PELATIHAN SELF MANAGEMENT UNTUK MENCEGAH PERILAKU BUNUH DIRI DI KALANGAN REMAJA - Wenny Hulukati; Maryam Rahim; Nurul Maulida Alwi; Rena Madina (Universitas Muhammadiyah Luwuk, 2023)
Suicide is often used as a way to cope with problems. This case often occurs in various circles, including adolescents. In an effort to prevent suicidal behavior among adolescents, a self-management training was conducted among adolescents in Kramat Village, Mananggu Subdistrict, Boalemo Regency. The training was conducted using demonstration and peer-counseling methods. The results of this training activity were: (1) increased participants' understanding of the importance of self-management and (2) increased skills in self-management among adolescents. The understanding of the importance of self management and the skills to do self management are expected to prevent adolescents from committing suicidal behavior and other dangerous and despicable acts in overcoming the problems they face.